INOVASI MAKANAN SELINGAN MPASI BERBASIS TAHU: STRATEGI PEMBERDAYAAN IBU BALITA UNTUK OPTIMALISASI GIZI ANAK - Restu Amalia Hermanto; Suci Amalia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The 6–24 month period is a critical phase in the First 1,000 Days of Life, significantly impacting child growth and development. Adequate complementary feeding with protein-rich snacks is essential to meet increased nutritional needs. Tofu, as a plant-based protein source, has potential as a nutritious complementary food for toddlers. This study aimed to improve mothers’ knowledge and skills in preparing tofu-based complementary foods through participatory training and demonstration. The intervention included nutrition education, practical tofu pudding preparation, and evaluation via observation, feedback, and group discussions involving 35 mothers in Sukajadi Village. Results showed improved understanding of tofu’s benefits and enhanced ability to prepare balanced complementary foods. The tofu pudding provided 137 kcal and 6.4 g protein per serving, fulfilling 10–15% of toddlers’ daily protein needs. Participants found the training practical, affordable, and effective in empowering them to prepare balanced complementary foods. This approach has potential to support improved child nutrition and stunting prevention in the community. Keywords: Complementary Feeding; Snacks; Tofu; 1000 days of life